Materials for Human Space Flight I: Book of Abstracts - Muhammad Musaddique Ali Rafique (Materials for Human Space Flight I: Book of Abstracts, 2021)
With continued interest in scientific community and general public in exploration and travel of space to micro and zero gravity to interplanetary voyages, need of materials and processes which make it happen has increased many folds. Though technology exist, which is enabling transportation of equipment and tooling (payload) to low to high earth orbits, there is still a gap in meeting with extreme harsh environments when it comes to transporting human to space. Materials for various part of rockets to their tailoring to optimization to enabling techniques which can make use of established metallurgical unit operations to be applied on existing primary (ores) and secondary (scrap) resources to extract materials which may be used as alloying elements in making of alloys for space exploration and flight exists. However, no actual account exists to make use of these metallurgical principals to extract and make alloys for human space travel and flights. This symposium is aimed to address this gap. A series of studies will be presented which will make use of basic intuition, thermodynamics, kinetics, and rate processes to extract important elements such as rare earths and add them as alloying elements to make superior high temperature alloys which will make actual human space flight possible. From he platform of Eastern Engineering Solutions Inc., we remain.